CALCULATION OF MAGNETIZING INRUSH CURRENT IN TRANSFORMER (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
When transformer is energized its current reaches very high value generally approximately 10 to 20 times greater than its rated current. This paper deals with study of calculation of inrush current in transformer. Different methods are available to calculate inrush current in transformer. Different methods to calculate inrush current in transformer which depends on operating conditions and type of transformer; which are explained in this paper.The calculation of inrush current is necessary is necessary to predefine the protective system adapted to power transformer.